Primer Screening for Dyera costulata (Miq) Hook.f Random Amplified Polymorphic DNA Analyses - YUYU SURYASARI POERBA; ELIZABETH ANITA WIDJAYA (Society for Indonesian Biodiversity, 2009)
Dyera costulata (Miq.) Hook.f (Apocynaceae) is a large tree of the lowland tropical rain forest of Southeast Asia, Thailand, Malay Peninsula and Indonesia, especially in Sumatra and Kalimantan (Borneo) islands. Its economic value was in its copious latex, used as gum in the manufacture of chewing gum. Today the timber of this species is much sought after for the manufacture of pencils and picture frames. Information on genetic diversity of the species is very limited. Hence studieswere initiated to screen primers for RAPD analyses of Dyera costulata for use in genetic variation studies. Seventy one Operon primers (10 mer) were used to generate a total of 864 consistent and ambiguous amplification products ranging from 200 bp to 2.0 kb. Rare and genotype specific bands were identified which could be effectively used to distinguish the genotypes. 34 highly polymorphic primers (100%) are recorded from 71 primers used. Three primers (OPA-04, OPU-06, and OPU-07) produced highest variable RAPD profiles. The dendrogram separated the 8 genotypes into 2 groups. Geneticdissimilarity ranged from 0.07 to 0.71 %.Key words: Dyera costulata, jelutong, primer screening, RAPD.